Tingkat Literasi Keuangan Syariah Pedagang Pasar di Kota Padangsidimpuan - Siregar, Rizal Ma'ruf Amidy (Jurnal Iqtisaduna, 2018)
Padangsidimpuan city as one of the cities in North Sumatra Province, is an integral part of advancing Islamic banking in Indonesia in general, and in North Sumatra in particular. The development of Islamic banking in Padangsidimpuan cannot be separated from the role of merchant as customers of Islamic banks in Padangsidimpuan, both as saving and financing customers. The biggest market in Padangsidimpuan is Sangkumpal Bonang and its surroundings, which is the center of economic activity of the city. This study aims to find out how the literacy level of Sangkumpal Bonang’s merchant to sharia financial products. This study discusses the difference in sharia financial literacy of Sangkumpal Bonang’s merchant based on age, the last education and the average incomes per month, using descriptive analysis methods and Chi-Square. This study proves that the higher the level of respondents formal education, the higher their sharia financial literacy rate. Likewise, the respondent's income level, the higher the average income per month, the higher their sharia financial literacy rate. While based on age, there is no difference in the level of respondents’ sharia financial literacy.